Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Pleistocene shifts in Great Basin hydroclimate seasonality govern the formation of lithium-rich paleolake deposits - Tripti Bhattacharya; Peter R. Brennan; Daniel E. Ibarra; Catherine A. Gagnon; Kristina L. Butler; Alexa Terrazas; Shaw Miller; Lee Ann Munk; David F. Boutt; Ran Feng; Stephanie N. Bullinger; Lucy Weisbeck (Quaternary Science Reviews, 2024)

Understanding mechanisms of racial disparities in breast cancer: an assessment of screening and regular care in the Carolina Breast Cancer Study - Matthew R. Dunn; Eman M. Metwally; Sanah Vohra; Terry Hyslop; Louise M. Henderson; Katherine Reeder-Hayes; Caroline A. Thompson; Jennifer Elston Lafata; Melissa A. Troester; Eboneé N. Butler (Cancer Causes & Control, 2024)

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Racial and ethnic differences in risk of second primary cancers among prostate cancer survivors - Diana R. Withrow; Sara J. Schonfeld; Rochelle E. Curtis; Lindsay M. Morton; Michael B. Cook; Eboneé N. Butler; Amy Berrington de González (Cancer Causes & Control, 2020)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Analytic laboratory performance of a point of care urine culture kit for diagnosis and antibiotic susceptibility testing - E. Bongard; N. Frimodt-Møller; M. Gal; M. Wootton; R. Howe; N. Francis; H. Goossens; C. C. Butler (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Integrating Top-Down and Bottom-Up Adaptation Planning to Build Adaptive Capacity: A Structured Learning Approach - J. R. A. Butler; R. M. Wise; T. D. Skewes; E. L. Bohensky; N. Peterson; W. Suadnya; Y. Yanuartati; T. Handayani; P. Habibi; K. Puspadi; N. Bou; D. Vaghelo; et al. (Coastal Management, 2015)

Sex differences in neuroadaptation to alcohol and withdrawal neurotoxicity - Lynda Sharrett-Field; Tracy R. Butler; Anna R. Reynolds; Jennifer N. Berry; Mark A. Prendergast (Pflügers Archiv - European Journal of Physiology, 2013)

Acute and Chronic Effects of Sodium Tungstate on an Aquatic Invertebrate (Daphnia magna), Green Alga (Pseudokirchneriella subcapitata), and Zebrafish (Danio rerio) - Leslie N. Clements; Ranulfo Lemus; Alicia D. Butler; Kate Heim; Matthew R. Rebstock; Carmen Venezia; Michael Pardus (Archives of Environmental Contamination and Toxicology, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Thinking and managing outside the box: coalescing connectivity networks to build region-wide resilience in coral reef ecosystems - R. S. Steneck; C. B. Paris; S. N. Arnold; M. C. Ablan-Lagman; A. C. Alcala; M. J. Butler; L. J. McCook; G. R. Russ; P. F. Sale (Coral Reefs, 2009)

Use of weighted reference panels based on empirical estimates of ancestry for capturing untyped variation - Matthew R. L. Egyud; Zofia K. Z. Gajdos; Johannah L. Butler; Sam Tischfield; Loic Le Marchand; Laurence N. Kolonel; Christopher A. Haiman; Brian E. Henderson; Joel N. Hirschhorn (Human Genetics, 2009)

Reproductive biology of the endangered Oxleyan pygmy perch Nannoperca oxleyana Whitley - J. T. Knight; G. L. Butler; P. S. Smith; R. N. E. Wager (Journal of Fish Biology, 2007)
The reproductive biology of the Oxleyan pygmy perch Nannoperca oxleyana is described from simultaneous studies of wild populations in north‐eastern New South Wales and mature fish held in aquaria. In the wild, 50% of males and females matured at total lengths of 24·0–25·9 and 28·0–29·9 mm, respectively. The species displays sexual dichromatism during the spawning season, with males developing more intense red and brown fin and body colouration, and black pelvic fins. Captive male broodfish displayed territoriality during the breeding season, closely guarding sites within artificial, plant‐like substrata in which pairs of fish spawned adhesive eggs. Protracted serial spawning of wild and captive fish occurred from September to April and May at mean water temperatures ≥16·6° C and day length ≥10·7 h. Captive broodfish spawned on an average of 57% of days during the 256 day spawning period. Gonado‐somatic indices averaged 0·7% for all ripe males and 4·1–4·2% for all ripe females collected. Mean total and batch fecundities of captive females were 1323 eggs per fish and 7·8 eggs per fish per day, respectively, and relative fecundity was 587 eggs g −1 of body mass. Batch fecundity of wild females was estimated at 7·8 eggs per fish. The adaptive significance of this reproductive strategy in a harsh, variable environment is discussed.

Changes in the innate immune response of Atlantic salmon, Salmo salar L., exposed to experimental infection with Neoparamoeba sp. - K A Gross; M D Powell; R Butler; R N Morrison; B F Nowak (Journal of Fish Diseases, 2005)
An experiment was conducted to determine the effect of Neoparamoeba sp. infection on the innate immune responses of Atlantic salmon. Atlantic salmon were experimentally infected with Neoparamoeba sp. and serially sampled 0, 1, 4, 6, 8 and 11 days post‐exposure (dpe). Histological analysis of infected fish gill arches identified the presence of characteristic amoebic gill disease lesions as early as 1 dpe with a steady increase in the number of affected gill filaments over time. Immune parameters investigated were anterior kidney phagocyte function (respiratory burst, chemotaxis and phagocytosis) and total plasma protein and lysozyme. In comparison with non‐exposed control fish basal respiratory burst responses were suppressed at 8 and 11 dpe, while phorbol myristate acetate‐stimulated activity was significantly suppressed at 11 dpe. Variable differences in phagocytic activity and phagocytic rate following infection were identified. There was an increase in the chemotactic response of anterior kidney macrophages isolated from exposed fish relative to control fish at 8 dpe. Total protein and lysozyme levels were not affected by Neoparamoeba sp. exposure.

Investigating the Relationship Between Site-specific Yield and Protein of Cereal Crops - S. Norng; A. N. Pettitt; R. M. Kelly; D. G. Butler; W. M. Strong (Precision Agriculture, 2005)

Atlantic salmon, Salmo salar L., previously infected with Neoparamoeba sp. are not resistant to re‐infection and have suppressed phagocyte function - K A Gross; R N Morrison; R Butler; B F Nowak (Journal of Fish Diseases, 2004)
Previous studies have indicated that Atlantic salmon, Salmo salar L., affected by amoebic gill disease (AGD) are resistant to re‐infection. These observations were based upon a comparison of gross gill lesion abundance between previously infected and naïve control fish. Anecdotal evidence from Atlantic salmon farms in southern Tasmania suggests that previous infection does not protect against AGD as indicated by a lack of temporal change in freshwater bathing intervals. Experiments were conducted to determine if previous infection of Atlantic salmon with Neoparamoeba sp. would provide protection against challenge and elucidate the immunological basis of any protection. Atlantic salmon were infected with Neoparamoeba sp. for 12 days then treated with a 4‐h freshwater bath. Fish were separated into two groups and maintained in either sea water or fresh water for 6 weeks. Fish were then transferred to one tank with a naïve control group and challenged with Neoparamoeba sp. Fish kept in sea water had lower mortality rates compared with first time exposed and freshwater maintained fish, however, these data are believed to be biased by ongoing mortalities during the seawater maintenance phase. Phagocyte function decreased over exposure time and freshwater maintained fish demonstrated an increased ability to mount a specific immune response. These results suggest that under the challenge conditions herein described, antigen exposure via infection does not induce protection to subsequent AGD.

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)